2007
DOI: 10.1152/ajpheart.00684.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-restricted angiotensin-converting enzyme overexpression causes conduction defects and connexin dysregulation

Abstract: (RAS) system activation is associated with an increased risk of sudden death. Previously, we used cardiac-restricted angiotensin-converting enzyme (ACE) overexpression to construct a mouse model of RAS activation. These ACE 8/8 mice die prematurely and abruptly. Here, we have investigated cardiac electrophysiological abnormalities that may contribute to early mortality in this model. In ACE 8/8 mice, surface ECG voltages are reduced. Intracardiac electrograms showed atrial and ventricular potential amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 64 publications
(102 reference statements)
6
45
1
1
Order By: Relevance
“…Through associated oxidative stress and unfavorable hemodynamic, metabolic, and cytokine influences, MetS leads to development of atrial fibrosis and slow conduction that can be visualized in LA voltage maps as areas of fractionated and low voltage potentials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Our study demonstrated that advanced electric remodeling and the presence of nonpulmonary vein substrate for AF must be expected in MetS and that the presence and extent of LA low voltage areas were associated with more AF recurrences, a finding supported by a previous study. 32 We suggest that in addition to PVI, extensive ablation to modify these low voltage areas may be necessary to achieve better long-term outcomes in patients with MetS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Through associated oxidative stress and unfavorable hemodynamic, metabolic, and cytokine influences, MetS leads to development of atrial fibrosis and slow conduction that can be visualized in LA voltage maps as areas of fractionated and low voltage potentials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Our study demonstrated that advanced electric remodeling and the presence of nonpulmonary vein substrate for AF must be expected in MetS and that the presence and extent of LA low voltage areas were associated with more AF recurrences, a finding supported by a previous study. 32 We suggest that in addition to PVI, extensive ablation to modify these low voltage areas may be necessary to achieve better long-term outcomes in patients with MetS.…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3][4][5] Renin-angiotensin system and oxidative stress can change the membrane ion channels and modulate the connexin surface expression, leading to slow atrial conduction. [6][7][8][9][10][11][12] This process called electroanatomic remodeling is frequently observed in patients with atrial fibrillation (AF). 13 Increased collagen deposition and matrix volume expansion has been found to correlate with the presence of AF and its persistence.…”
mentioning
confidence: 99%
“…Ang II-induced gap junction dyslocalization in untreated dTGRs was probably due to changes in the Cx43 phosphorylation state. 30 Cx43 redistribution also occurs under conditions of ischemia and contributes to electrical uncoupling of cardiomyocytes and the development of arrhythmias. Cardiac preconditioning was shown to prevent intracellular Cx43 redistribution and to protect against cardiac injury and arrhythmias during subsequent attacks of prolonged ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these, such as high glucose, PKC expression/activity, and oxidative stress, are implicated in diabetic pathology (19,24,50). Importantly, gap junction remodeling, which occurs with many cardiac pathologies (6,38), may be triggered by elevated angiotensin (12,22). Thus gap junction remodeling is blocked by inhibition of angiotensin formation or by receptor blockade (7,9).…”
mentioning
confidence: 99%